Static magnetic field enhances the viability and proliferation rate of adipose tissue-derived mesenchymal stem cells potentially through activation of the phosphoinositide 3-kinase/Akt (PI3K/Akt) pathway. (2nd January 2017) - Marędziak, Monika; Tomaszewski, Krzysztof; Polinceusz, Paulina; Lewandowski, Daniel; Marycz, Krzysztof
ABSTRACT: The aim of this work was to investigate the effects of 0.5T static magnetic field (sMF) on the viability and proliferation rate of human adipose-derived mesenchymal stromal stem cells (hASCs) via activation of the phosphoinositide 3-kinase/Akt (PI3K/Akt) signaling pathway. In a 7-d culture we examined cell growth kinetic and population doubling time (PDT). We also examined cell morphology and the cellular senescence markers level. Exposure to sMF enhanced the viability of these cells. However, the effect was blocked by treating the cells with LY294002, a P13K inhibitor. We compared this effect by Western Blot analysis of Akt protein expression. We also examined whether the cell response on sMF stimulation is dependent on integrin engagement and we measured integrin gene expression. Our results suggest that stimulation using sMF is a viable method to improve hASC viability. sMF is involved in mechanisms associated with controlling cell proliferative potential signaling events.